Population Ageing and the Ecology in China: Towards a Balanced Developmental Strategy Model - Guo, X.; Marinova, Dora; Jia, R. (The Modelling and Simulation Society of Australia and New Zealand Inc., 2011)
As the most populous country in the world, China is enjoying unprecedented economic growth, but this development has caused serious degradation of the country’s physical environment. The issues are particularly aggravated with China’s quickly expanding urbanisation and ageing population. Based on recent data, this paper analyses China’s demographic profile and explores the country’s ecological deterioration issues in order to seek a balanced economic developmental strategy model. Through cluster analysis, the paper explores the influences of population change and economic growth on the environment with the purpose of providing some valuable knowledge and lessons for achieving a quality economic growth for China. It argues that changes have to be made to ease the double burden of restoring the deteriorating ecosystems and dealing with the ageing crisis in the country.